2013
DOI: 10.1038/ncomms2408
|View full text |Cite
|
Sign up to set email alerts
|

The phosphatase Dullard negatively regulates BMP signalling and is essential for nephron maintenance after birth

Abstract: Most kidney nephron components, including glomeruli and renal tubules, derive from the metanephric mesenchyme. The overall differentiation into each component finishes at birth, but the molecular events linking the perinatal and adult kidneys remain elusive. Dullard was cloned from Xenopus kidneys, and encodes a phosphatase that negatively regulates BMP signalling. Here we report that Dullard deletion in the murine metanephric mesenchyme leads to failure of nephron maintenance after birth, resulting in lethali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 40 publications
(46 reference statements)
0
41
0
Order By: Relevance
“…More recent studies in postnatal mouse nephron development22 and wing vein formation in Drosophila 23 also supported the finding that Dullard was a negative regulator of the BMP pathway. However, in these two latter studies a mechanistic link to the BMP pathway was not demonstrated as they focused on a thorough analysis of genetic interactions between Dullard and the BMP pathway.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…More recent studies in postnatal mouse nephron development22 and wing vein formation in Drosophila 23 also supported the finding that Dullard was a negative regulator of the BMP pathway. However, in these two latter studies a mechanistic link to the BMP pathway was not demonstrated as they focused on a thorough analysis of genetic interactions between Dullard and the BMP pathway.…”
Section: Discussionmentioning
confidence: 57%
“…Dullard, a member of the DXDX(T/V) phosphatase family has been previously shown to inhibit BMP signaling in Xenopus embryos by causing the dephosphorylation of type I BMP receptors and the ubiquitin-dependent proteasomal degradation of the BMP type II receptors21. Two more recent reports in mice and Drosophila mutants demonstrate Dullard negatively regulates BMP signaling, however the focus of these studies were to describe genetic interactions between BMP and Dullard, and therefore, insights into the mechanistic interaction of Dullard with BMP remain to be described2223. Our findings add new insights into the role Dullard plays during BMP signaling during Drosophila development.…”
mentioning
confidence: 99%
“…Rescue of renal agenesis in these mutants has been achieved by genetically reducing BMP levels 48,50 thus linking apoptosis with increased BMP signalling. A pro-apoptotic action of pSMAD signalling at later stages of kidney development has also been reported in mice carrying mutations in the phosphatase Dullard, a negative regulator of the pSMAD pathway 51 . Analogously, we argue here that the strong increase of pSMAD in Wt1 À / À MM is a major factor involved in apoptosis of Wt1 mutant mesenchyme.…”
Section: Discussionmentioning
confidence: 99%
“…The gene encoding the phosphatase Dullard, which dephosphorylates BMP type I receptors and promotes proteasomal degradation of BMP type II receptors, is expressed in cap mesenchyme [31]. Mice in which Ctdnep1 (dullard) has been inactivated specifically in this population display severe malformations of the juvenile kidney, but unperturbed embryonic kidney development [32]. This suggests either that restriction of receptor-mediated phosphorylation is not the mechanism that limits SMAD1/5 signaling in the cap mesenchyme, or that there is compensation by a redundant phosphatase.…”
Section: Bone Morphogenetic Protein (Bmp) Signaling In Embryonic Nephmentioning
confidence: 99%